PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI - Damingun Damingun (Universitas Muhammadiyah Kalimantan Timur, 2017)
Competence is an underlying characteristics of an individual which is causally related to criterion-referenced effective and or superior performance in a job situation. Human resources - based competence is urgently needed in business competitive era. So, employee development program became the most challenge for each organization to increase performance organization.